Synthesis of Raspberry-Like SiO2–TiO2 Nanoparticles toward Antireflective and Self-Cleaning Coatings - Li, Xiaoyu; He, Junhui (ACS applied materials & interfaces, 2013)
Silica–titania core–shell nanoparticles of 30, 40, 50, 55, 75, and 110 nm were prepared from tetraethyl orthosilicate (TEOS) and tetraisopropyl titanate (TIPT). After calcination, the amorphous titania shell transformed into anatase nanoparticles, and the silica–titania core–shell nanoparticles became raspberry-like nanoparticles. These nanoparticles were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, and UV–vis spectroscopy. Hierarchically structured antireflective and self-cleaning particulate coatings were fabricated on glass substrates via layer-by-layer (LbL) assembly using silica–titania core–shell nanoparticles and silica nanoparticles as building blocks followed by calcination. The maximum transmittance of coated glass substrates reached as high as ca. 97%, while that of the glass substrates is only ca. 91%. The morphologies of the coatings were observed by SEM and atom force microscopy (AFM). Such hierarchically structured raspberry-like SiO2–TiO2 nanoparticle coatings had superhydrophilic and antifogging properties. The coatings also showed photocatalytic activity toward organic pollutants and thus a self-cleaning property.